Nuclear Receptors: Mechanistic Insights into Endocrine Resistance in Prostate and Breast Cancers - Macrina Beatriz Silva-Cázares; Stephanie I. Nuñez-Olvera; Ricardo Hernández-Barrientos; Enoc Mariano Cortés-Malagón; María Elizbeth Alvarez-Sánchez; Jonathan Puente-Rivera (Receptors)
This review focuses on the pivotal roles of nuclear receptors (NRs) in driving endocrine resistance in prostate and breast cancers. In prostate cancer (PCa), androgen receptor (AR) amplification, mutations, and altered coactivator interactions sustain tumor growth under androgen deprivation therapy (ADT), leading to castration-resistant prostate cancer (CRPC). Orphan NRs like RORβ, TLX, and COUP-TFII further contribute to CRPC by regulating stemness and therapeutic resistance mechanisms. In breast cancer, NRs, including estrogen receptor alpha (ERα), androgen receptor (AR), glucocorticoid receptor (GR), and liver receptor homolog-1 (LRH-1), modulate estrogen signaling pathways and alternative survival mechanisms like PI3K/AKT/mTOR and NFκB, promoting resistance to endocrine therapies such as tamoxifen. Understanding these NR-mediated mechanisms is critical for developing targeted therapies to overcome endocrine resistance and improve patient outcomes in hormone-dependent cancers.